A computational study on the uncertainty quantification of failure of clays with a modified Cam-Clay yield criterion - Ambrosios A. Savvides; Manolis Papadrakakis (SN Applied Sciences, 2021)
Abstract In this study, the quantitative effect of the random distribution of the soil material properties to the probability density functions of the failure load and displacements is presented. A modified Cam-Clay failure criterion is embedded into a stochastic finite element numerical tool for this purpose. Various assumptions for the random distribution of the compressibility factor $$κ$$ κ , of the constitutive relation, the critical state line inclination c of the soil, and the permeability k have been tested and assessed with Latin hypercube sampling followed by Monte Carlo simulation. It is confirmed that both failure load and displacements follow Gaussian normal distribution despite the nonlinearity of the problem. Moreover, as the soil depth increases the mean value of failure load decreases and the failure displacement increases. Consequently, failure mechanism of clays can be determined in this work within an acceptable variability, taking into account the soil depth and nonlinear constitutive relations which in the analytical solutions is not feasible as it is assumed the Meyerhoff theory which considers the elastic halfspace.